Estudo sobre o comportamento do gerador a relutância variável operando no modo autoexcitado - Bernardeli, Victor Régis (2014)
Operation of a switched reluctance machine (SRM) as a self-excited generator is focused in this work. The investigation is supported by a thorough literature review, and uses a mathematical model that accounts for the non linearity between flux linkages and currents, a requirement to correctly represent the generator operation in the proposed mode. The method chosen to start the process of self excitation is the use of a partially charged capacitor, placed in parallel with the generator phases and also with the electrical load. This capacitor is also used to smooth the steady state D.C. generated voltage, delivered to the load. Beyond generated voltage build up characteristics, a comprehensive investigation on the generator operation, considering different primary speeds, variable primary speeds, different electrical loads, load rejection, phase loss is carried out. Generated voltage and current control circuits to accommodate the generator operation are proposed. A bench test platform developed to verify the theoretical finds is used and all the results obtained in the work are experimentally checked and found to be in good accordance with theoretical expectations. As a whole, the investigation shows that the use of SRM as a self excited generator is rather feasible and does not require unattainable circuitry or control strategies.